The Inherent Reward of Choice - Leotti, Lauren A.; Delgado, Mauricio R. (Psychological Science, 2011)
Research suggests that the exercise of control is desirable and adaptive, but the precise mechanisms underlying the affective value of control are not well understood. The study reported here characterized the affective experience of personal control by examining the neural substrates recruited when individuals anticipate the opportunity to make a choice—in other words, when they anticipate the means for exercising control. We used an experimental paradigm that probed the value of having a choice. Participants reported liking cues that predicted a future opportunity to make a choice more than cues that predicted no choice. The anticipation of choice itself was associated with increased activity in corticostriatal regions, particularly the ventral striatum, involved in affective and motivational processes. This study is the first direct examination of the affective value of having the opportunity to choose. These findings have important implications for understanding the role of perception of control, and choice itself, in self-regulatory processes.